The official CHFI study guide (Exam 312-49) : for computer hacking forensic investigator. - Kleiman, Dave (Syngress, 2007)
This is the official CHFI study guide for professionals studying for the forensics exams and for professionals needing the skills to identify an intruder's footprints and to properly gather the necessary evidence to prosecute. The EC-Council offers certification for ethical hacking and computer forensics. Their ethical hacker exam has become very popular as an industry gauge and we expect the forensics exam to follow suit. The material is presented in a logical learning sequence: a section builds upon previous sections and a chapter on previous chapters. All concepts, simple and complex, are defined and explained when they appear for the first time. This book includes the following special chapter elements: Exam objectives covered in a chapter are clearly explained in the beginning of the chapter, Notes and Alerts highlight the crucial points, Exams Eye View section at the end of each chapter emphasizes the important points from the exams perspective, Key Terms present the definitions of key terms used in the chapter, Review Questions section at the end of each chapter that contains the questions modeled after the real exam questions based on the material covered in the chapter. The answers to these questions are presented with explanations in an appendix. Also included is a full practice exam modeled after the real exam. The answers to the exam questions are presented with full explanations. * The only study guide for CHFI, provides 100% coverage of all exam objectives. * Full web-based practice exam with explanations of correct and incorrect answers * Forensics xxxxx.